ICT4Ag: Making it happen - Addom, Benjamin K.; Rambaldi, Giacomo (Technical Centre for Agricultural and Rural Cooperation, 2013)
The 2013 ICT4Ag conference in Rwanda was unique in that it brought together the ICT and agricultural sectors. Its success will be measured by the action taken by delegates after the conference based on a clear list of action points for the community